An FGFR3/MYC positive feedback loop provides new opportunities for targeted therapies in bladder cancers. Issue 4 (20th February 2018) - Mahe, Mélanie; Dufour, Florent; Neyret‐Kahn, Hélène; Moreno‐Vega, Aura; Beraud, Claire; Shi, Mingjun; Hamaidi, Imene; Sanchez‐Quiles, Virginia; Krucker, Clementine; Dorland‐Galliot, Marion; Chapeaublanc, Elodie; Nicolle, Remy; et al.
Abstract: FGFR3 alterations (mutations or translocation) are among the most frequent genetic events in bladder carcinoma. They lead to an aberrant activation of FGFR3 signaling, conferring an oncogenic dependence, which we studied here. We discovered a positive feedback loop, in which the activation of p38 and AKT downstream from the altered FGFR3 upregulates MYC mRNA levels and stabilizes MYC protein, respectively, leading to the accumulation of MYC, which directly upregulates FGFR3 expression by binding to active enhancers upstream from FGFR3 . Disruption of this FGFR3/MYC loop in bladder cancer cell lines by treatment with FGFR3, p38, AKT, or BET bromodomain inhibitors (JQ1) preventing MYC transcription decreased cell viability in vitro and tumor growth in vivo . A relevance of this loop to human bladder tumors was supported by the positive correlation between FGFR3 and MYC levels in tumors bearing FGFR3 mutations, and the decrease in FGFR3 and MYC levels following anti‐FGFR treatment in a PDX model bearing an FGFR3 mutation. These findings open up new possibilities for the treatment of bladder tumors displaying aberrant FGFR3 activation. Synopsis: In bladder carcinoma, alterations of FGFR3 receptor are often observed and lead to constitutive activation and oncogene addiction, which can be targeted with a pan‐FGFR inhibitor. Our identification and characterization of a FGFR3/MYC positive feedback loop opens new avenues for targeted therapies. MYC is a key master regulator of proliferation activated by aberrantly activated FGFR3. FGFR3‐dependent MYC accumulation is dependent on p38, which regulates MYC mRNA levels, and AKT, which stabilizes MYC protein. FGFR3 is directly targeted by MYC. Disrupting the FGFR3/MYC loop using FGFR3, p38, AKT, or BET bromodomain inhibitors decreases cell viability and tumor growth in FGFR3‐dependent cell lines. Evidence for the relevance of the FGFR3/MYC feedback loop to human tumors is provided by the decrease in both FGFR3 and MYC levels induced by a pan‐FGFR inhibitor in a PDX model bearing an FGFR3 mutation, and by the positive correlation between MYC and FGFR3 levels in human tumors with FGFR3 mutations. Abstract : In bladder carcinoma, alterations of FGFR3 receptor are often observed and lead to constitutive activation and oncogene addiction, which can be targeted with a pan‐FGFR inhibitor. Our identification and characterization of a FGFR3/MYC positive feedback loop opens new avenues for targeted therapies.